VANET-Based Traffic Monitoring and Incident Detection System: A Review - Mustafa Maad Hamdi; Lukman Audah; Sami Abduljabbar Rashid; Sameer Alani (International Journal of Electrical and Computer Engineering (IJECE), 2021)
As a component of intelligent transport systems (ITS), vehicular ad hoc network (VANET), which is a subform of manet, has been identified. It is established on the roads based on available vehicles and supporting road infrastructure, such as base stations. An accident can be defined as any activity in the environment that may be harmful to human life or dangerous to human life. In terms of early detection, and broadcast delay. VANET has shown various problems. The available technologies for incident detection and the corresponding algorithms for processing. The present problem and challenges of incident detection in VANET technology are discussed in this paper. The paper also reviews the recently proposed methods for early incident techniques and studies them.